Hepatoma. Experience in Cali (Colombia Medica, 1986)
59 cases of primary hepatic tumors were retrospectively analyzed at the Hospital Universitario del Valle, Cali, Colombia, between 1953 and 1984. Their clinical, biochemical, and pathological characteristics were described. These findings are compared with those of other series published in different parts of the world.